Replication of Colicin E1 Plasmid DNA in Cell Extracts - Sakakibara, Yoshimasa (1974)
Cell extracts were prepared from Escherichia coli carrying colicin E1 plasmid. The DNA in extracts was almost exclusively closed-circular DNA of the plasmid. Labeled deoxyribonucleotides were incorporated into DNA in extracts. DNA of colicin E1 plasmid was the sole DNA product, and was composed of completely replicated molecules and a class of replicative intermediates. The intermediates carried an average of approximately two pieces of DNA fragments that had a sedimentation coefficient of approximately 6 S and were not covalently attached to the parental DNA strands. The replication was initiated on closed-circular molecules and the complete molecules were synthesized semiconservatively. The DNA synthesis depended on the four ribonucleoside triphosphates and was sensitive to rifampicin. A round of DNA replication, once initiated, was completed in the presence of rifampicin, indicating that RNA synthesis is involved in the initiation of replication of the plasmid DNA. Most of the replicated molecules were isolated in super-coiled structures. These results indicate that this soluble system is capable of carrying out a complete round of replication of colicin E1 plasmid DNA.